Analysis of Digital Marketing Sector - Das, Jyotiranjan (International Journal of Psychosocial Rehabilitation, 2019)
The piece of research study seeks to clarify the preferred strategies used for advertising in digital media. Some new methods used to support and market products in the Internet age. "Desk research" has become "digital research," product analysis has now become possible through internet research. For competitive advantage, most Indian businesses use digital marketing. Social media has gained prominence rapidly as it allows people to communicate and share content and topics. The growth of IT, driven by the advent of digital communication technologies, has enabled companies to change the way of service is communicated. Digital communications marketing strategy is a technique to use digital media. The purpose of the study undertaken is to examine the effectiveness of digital media advertising online as well as emerging marketing media options. This paper primarily studies the creation history of digital marketing and current context, including the disparity and interaction between digital marketing and conventional advertising, as well as the relationship between internet industry and the digital marketing. The paper assist small businesses and start-ups to effectively incorporate and execute digital marketing as a tactic in their business plan and understand the importance of digital marketing in the competitive marketplace.